Assessment of parasympathetic autonomic functions in ulcerative colitis patients - AL-Hillawi, Ahmed H.; AL-Dhahir, Hawa A.; Ghadban, Jasim M. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Ulcerative colitis has been reported to be associated with autonomic dysfunction, mainly of vagal involvement. Objectives: To Determine whether there is a parasympathetic dysfunction in ulcerative colitis patients in remission state or not. Results: For all of the three tests, patients group gave significantly lower results (P˂ 0.05) which was the least level of significance. Materials and methods: Three standardized tests of parasympathetic function, based on heart rate variation in response to certain stimuli (heart rate response to Valsalva maneuver, to deep breathing and to standing from supine position) were used on 54 ulcerative colitis patients in remission, and 41 healthy volunteers as a control group. Conclusion: Ulcerative colitis is associated with vagal dysfunction which could be a hidden cause for the underlying inflammatory status because of the recently established anti-inflammatory role of vagus nerve.